(untitled) (Research, Society and Development, 2025)
Introduction: Bruton’s disease (BD) or X-linked agammaglobulinemia is characterized by the patient’s inability to produce antibodies. Immunological vulnerability combined with inadequate oral hygiene, makes the oral environment more conducive to bacterial proliferation. Objective: To conduct an integrative review of the oral manifestations affecting patients with BD. Methods: A search was carried out in the BVS, CAPES Journals, and PubMed databases using the descriptors: Agammaglobulinemia, Oral Health, Oral Manifestations, Dental Caries, and Periodontal Disease. The PICOT strategy guided the research and the selection process was performed in pairs. Results: A total of 180 articles were identified, of which five were included in the final sample. The described alterations included aphthous ulcers, herpes infections, candidiasis, tonsillitis, gingivitis, and dental calculus. Pseudomonas sepsis occurred in one case report, presenting with injected tonsils with exudates, ulcerated tongue, and edematous upper lip with erythematous induration and crusts that progressed to oral ulcers and ecthyma gangrenosum. Significantly higher levels of lactobacilli and yeasts were found in the oral cavity of these patients compared with individuals with selective IgA deficiency and with healthy controls. Alveolar bone resorption of the maxillary incisors, multiple carious lesions, and marginal gingivitis along the dental arch were observed in a patient with BD associated with Trisomy 21. Conclusion: Individuals with BD may present alterations that compromise not only oral health but also contribute to the worsening of systemic conditions. Early diagnosis, immunoglobulin replacement therapy, and the maintenance of adequate oral hygiene may result in better oral health outcomes.